2017
DOI: 10.1016/j.tourman.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Scuba diving tourism systems and sustainability: Perceptions by the scuba diving industry in two Marine Protected Areas

Abstract: The scuba diving tourism industry's sustainability is affected by various problems. •These problems were investigated by engaging scuba diving operators in two MPAs.• Relations with other elements in the Scuba Diving Tourism System were assessed.• Operators felt the potential of the scuba diving industry, yet limited support.• General and ad hoc measures to enhance the industry's sustainability were advanced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 23 publications
4
69
0
7
Order By: Relevance
“…Portofino may be perceived as a case where the promotion of sustainable resource uses is not required, thanks to a variety of resources already made available to clients and staff by local municipalities. Nevertheless, scuba divers visiting the area often do so exclusively to dive, thus only coming into contact with the scuba diving operations during their stay (Lucrezi et al, 2017). Actions like throwing a cigarette butt into the sea and disposing of plastic and cans in the regular waste were observed at dive centres which, during this study, supported the importance of sustainability (S. Lucrezi pers.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Portofino may be perceived as a case where the promotion of sustainable resource uses is not required, thanks to a variety of resources already made available to clients and staff by local municipalities. Nevertheless, scuba divers visiting the area often do so exclusively to dive, thus only coming into contact with the scuba diving operations during their stay (Lucrezi et al, 2017). Actions like throwing a cigarette butt into the sea and disposing of plastic and cans in the regular waste were observed at dive centres which, during this study, supported the importance of sustainability (S. Lucrezi pers.…”
Section: Discussionsupporting
confidence: 72%
“…Scuba diving operations revolving around two Marine Protected Areas (MPAs), one in Mozambique and one in Italy, were selected for this study (Figure 1). Past and present environmental and ecological issues associated with the marine and coastal environments at the case studies are outlined by Lucrezi et al (2017) and briefly described below. The relevant policies affecting scuba diving tourism operations at the case studies are listed in Table 1.…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Anchoring must therefore be banned, and recreational boating regulated (Venturini et al, ). Pleasure crafts could be allowed to moor to buoys installed for this purpose, which would be especially useful for diving centres: if correctly managed, scuba‐diving tourism represents a sustainable activity that generates revenue and supports local communities (Lucrezi et al, ), and may even actively support conservation (Cerrano, Milanese, & Ponti, ). Inspections in 2016 showed that derelict fishing gear caused a severe impact on epibenthic communities, suggesting that all forms of bottom fishing must be banned and recreational fishing should be strictly regulated (Venturini, Campodonico, Cappanera, Fanciulli, & Cattaneo‐Vietti, ).…”
Section: Discussionmentioning
confidence: 99%
“…Gatti et al (2017) collated all the available information on Portofino reefs, starting from the pioneer studies of Tortonese, to build a large dataset of descriptive and semi-quantitative data, which allowed exploring the evolution of the rocky reef sessile assemblages across nearly 60 years. A major change of community composition was evidenced in the 1980-90s, under the combined effects of climate warming and increased human pressures, especially diving tourism (Lucrezi et al 2017). Some species disappeared or got rarer, many found refuge at depth, and among the newcomers there were recently introduced alien species.…”
Section: Rocky Reefsmentioning
confidence: 99%